The influence of experience and environments on usability and user experience in a wheelchair simulator - Emilia Biffi; Sara Arlati; Luca Negri; Marta Mondellini; Chiara Genova; Matteo Malosio; Claudio Corbetta; Angelo Davalli; Marco Sacco (Annals of Medicine, 2025)
Background The number of people who require a wheelchair is rising due to an increased number of injuries and the growing number of elderly. Training of new wheelchair users is mandatory to let them feel independent and safe. Virtual reality (VR)-based wheelchair simulators allow training wheelchair skills in a controlled, safe, and repeatable environment. Our group recently developed a wheelchair simulator for a motion platform in semi-immersive VR.Objective To assess the usability and user experience of two VR-based training environments in 20 participants considering the sense of presence, the cybersickness, the suitability of VR system, and the performance and to assess if these evaluations are influenced by the expertise in the use of a wheelchair.Materials and Methods The simulator was composed of a moving platform, an adaptable wheelchair, and two VR environments (one outdoor - OE, one indoor - IE) projected on a 180° screen. 10 able-bodied volunteers (wheelchair naïve-users, WNUs) and 10 expert wheelchair users (WUs) due to spinal cord injury were recruited. They performed one session during which they tested the indoor (IE) and the outdoor (OE) VR environment. Measures to assess user experience, such as the System Usability Scale, the Technological Acceptance Measure, and the Suitability Evaluation Questionnaire were administered.Results The usability of WUs was high in both environments, while WNUs had some difficulties in IE navigation. Acceptance (TAM mean score) was significantly higher for the OE (p-value = 0.017) in both groups (WNU-OE: 5.11 ± 0.44; WU-OE: 5.18 ± 0.67; WNU-IE: 4.75 ± 0.47; WU-IE: 4.85 ± 0.62). Suitability was higher for OE and generally higher for WUs.Conclusion Our study focused on user experience during VR-powered wheelchair navigation in both WUs and naïve ones. The system proved to be engaging and caused low cybersickness effects. Future works will focus on longer training and will assess performance improvements longitudinally.